2014
DOI: 10.1002/2014ja020156
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prolonged southward interplanetary magnetic field on low‐latitude ionospheric electron density

Abstract: The present work describes the low-latitude ionospheric variability during an unusually prolonged (~33 h) geomagnetically disturbed condition that prevailed during 15-16 July 2012. The low-latitude electron density in summer hemisphere, investigated using ground-and satellite-based observations, responded to this by generating strong negative ionospheric storm on 16 July. The maximum electron density on 16 July over Indian low latitudes was reduced by more than 50% compared to that on a geomagnetically quiet d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 45 publications
(53 reference statements)
1
21
0
Order By: Relevance
“…The disappearance of the one or two crests is most likely caused by the disturbed electric fields in the low‐latitude and equatorial regions. The effects of the neutral composition disturbance to the depletion in both the topside and bottomside TEC are mainly reflected in the region from 10°N to 50°N, which are consistent with the TIMED/GUVI [O]/[N 2 ] [ Bagiya et al , ; Liu et al , ]. The decline in TEC of the south of 20°S is inconspicuous.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…The disappearance of the one or two crests is most likely caused by the disturbed electric fields in the low‐latitude and equatorial regions. The effects of the neutral composition disturbance to the depletion in both the topside and bottomside TEC are mainly reflected in the region from 10°N to 50°N, which are consistent with the TIMED/GUVI [O]/[N 2 ] [ Bagiya et al , ; Liu et al , ]. The decline in TEC of the south of 20°S is inconspicuous.…”
Section: Resultssupporting
confidence: 76%
“…As shown in Figure , the intense ionospheric negative storm effects on 16 July obviously appear at all the 17 stations in this sector. Bagiya et al [] and Liu et al [] reported the [O]/[N 2 ] data obtained from Thermosphere, Ionosphere, Mesosphere Energetics and Dynamics (TIMED)/Global Ultraviolet Imager (GUVI) showing the neutral composition disturbance zone (depleted [O]/[N 2 ]) over this region on 16 July. It is generally accepted that the ionospheric negative storms should be caused by the changes in the neutral composition due to the heating of the thermosphere during the geomagnetic storms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both M‐class flares of 7 September were accompanied by IEF y enhancements (shaded region in Figure a) associated with the intensification of southward IMF B z . The IEF y fluctuations driven by southward IMF B z results in eastward electric field penetration during daytime and thus enhances the E region current (e.g., Bagiya et al, , ; Hui et al, , and references therein). Therefore, we suggest that the EEJ current variations during two M‐class flares on 7 September contain contributions from both flare as well as eastward IEF y penetration.…”
Section: Discussionmentioning
confidence: 99%
“…The excess joule heating over high latitudes during a storm strengthens the upward vertical wind, which raises thermospheric molecular rich air to higher altitudes (Immel et al, ). The meridional wind along with the diurnal wind transports the enhanced thermospheric mean molecular mass (e.g., Prölss, ) toward mid and low latitudes (e.g., Bagiya et al, ; Fuller‐Rowell et al, ; Roble et al, , and references therein). The initial transport enhances the [O/N 2 ] at low latitudes, which results into enhanced ionospheric density (through photoionisation of atomic oxygen), while the molecules that arrive later in time reduce electron density by enhancing the recombination rate with ambient N 2 + and O 2 + (e.g., Bagiya et al, , ; Burns et al, ; Liou et al, ; Strickland et al, ).…”
Section: Discussionmentioning
confidence: 99%